2001
DOI: 10.1080/00016350152509201
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of utilization of dental services among 20- to 34-year-old Danes

Abstract: Our aim was to identify determinants of utilization of dental services among 20- to 34-year-old Danes as outlined in a conceptual framework. Our sample consisted of a sample of 464 individuals who had been interviewed by 10 experienced interviewers from The Danish National Institute of Social Research. Our questionnaire comprised a battery of questions based on our conceptual model. The analysis was done in a hierarchical manner using a framework with three steps: Predisposing factors --> Enabling factors --> … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 14 publications
1
29
0
3
Order By: Relevance
“…A range of socio-demographic, behavioral and psychosocial factors have been related to dental anxiety [3-5]. Dental anxiety is one of several factors related to whether or not people attend dental care [6]. The relationship between dental anxiety and irregular dental attendance and avoidance of dental care is well established [7-10], and also the differences by gender and age, with higher prevalence of dental anxiety in women than in men [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of socio-demographic, behavioral and psychosocial factors have been related to dental anxiety [3-5]. Dental anxiety is one of several factors related to whether or not people attend dental care [6]. The relationship between dental anxiety and irregular dental attendance and avoidance of dental care is well established [7-10], and also the differences by gender and age, with higher prevalence of dental anxiety in women than in men [2].…”
Section: Introductionmentioning
confidence: 99%
“…Using Aday and Andersen's framework for the study of access to medical care [24], Scheutz and Heidmann [6] explored determinants of utilization of dental care among 20-34-year olds. They found that in Denmark the following factors were associated with irregular use of dental services: age, sex, exercise habits, costs, dental anxiety, and perceived own dental health.…”
Section: Introductionmentioning
confidence: 99%
“…Este cambio puede ser valorado de acuerdo al punto de vista del profesional (valoración técnica o normativa), o bien según la percepción del individuo enfermo y su familia (valoración subjetiva, o sentida/expresada). Este modelo teórico se ha utilizado en estudios sobre servicios odontológicos en diversos escenarios 22,23,24,35,39,40,41 . Dentro de este modelo es posible estudiar al mismo tiempo la existencia de desigualdades en salud, ya que en él se incluyen variables socioeconómicas, donde si existiese desigualdad socioeconómica sería viable identificarla.…”
Section: Introductionunclassified
“…Several studies have identified the determinants of dental service utilization among adults around the world. Some of them are age, sex, race, ethnicity, cost of dental treatment, health insurance, dental anxiety, hygiene habits, oral health education, oral health beliefs, self-reported oral health problems, and need for oral health [Rosenstock, 1966;Scheutz and Heidmann, 2001;Pohjola et al, 2007;Slack-Smith et al, 2007;Araújo et al, 2009; Baker, Keywords Dental care · Dental health services · Oral health · Pregnancy · Review Abstract Despite the fact that dental care attendance during pregnancy has been recommended by guidelines and institutions, the demand for dental services is still low among pregnant women. The aim of this study was to identify and analyze the determinants of dental care attendance during pregnancy.…”
mentioning
confidence: 99%